Nonlinear Optical Signal Processing for Tbit/s Ethernet Applications - L. K. Oxenløwe; M. Galili; H. C. Hansen Mulvad; H. Hu; J. L. Areal; E. Palushani; H. Ji; A. T. Clausen; P. Jeppesen (International Journal of Optics)
We review recent experimental demonstrations of Tbaud optical signal processing. In particular, we describe a successful 1.28 Tbit/s serial data generation based on single polarization 1.28 Tbaud symbol rate pulses with binary data modulation (OOK) and subsequent all-optical demultiplexing. We also describe the first error-free 5.1 Tbit/s data generation and demodulation based on a single laser, where a 1.28 Tbaud symbol rate is used together with quaternary phase modulation (DQPSK) and polarization multiplexing. The 5.1 Tbit/s data signal is all-optically demultiplexed and demodulated by direct detection in a delay-interferometer-balanced detector-based receiver, yielding a BER less than 10−9. We also present subsystems making serial optical Tbit/s systems compatible with standard Ethernet data for data centre applications and present Tbit/s results using, for instance silicon nanowires.